Thin Layer Chromatographic Analysis of Beta-Lactam Antibiotics - Gabriel Hancu; Brigitta Simon; Hajnal Kelemen; Aura Rusu; Eleonora Mircia; Árpád Gyéresi (Tabriz University of Medical Sciences, 2013)
Purpose: The paper describes some thin layer chromatographic procedures that allow simple and rapid separation and identification of penicillins and cephalosporins from complex mixtures. Methods: Using silicagel GF254 as stationary phase and selecting different mobile phases we succeeded in the separation of the studied beta-lactamins. Our aim was not only to develop a simple, rapid and efficient method for their separation but also the optimization of the analytical conditions. Results: No system will separate all the beta-lactams, but they could be identified when supplementary information is used from color reactions and/or by using additional chromatographic systems. Conclusions: The right combination of solvent system and detection method allows the identification of the studied penicillins and cephalosporins and can be successfully used in the preliminary analysis beta-lactam antibiotics.